Prevalence and factors associated with erectile dysfunction among males with human immunodeficiency virus in a tertiary teaching hospital in Malaysia - Enoma, Aghahowa (2016)
Erectile dysfunction (ED) has been associated with the treatment of human immunodeficiency virus (HIV) and some other chronic diseases. Study on ED is still scanty in Malaysia, particularly among male HIV patients and, ED appears to be under-reported. The aim of this study is to determine the prevalence and factors associated with ED among male HIV patients in University Malaya Medical Centre. A cross sectional study was conducted among male HIV patient on highly active anti-retroviral therapy (HAART) attending the outpatient clinic of a teaching hospital in West Malaysia. A systematic random sampling method was employed for the selection of respondents, participants were interviewed using a structured questionnaire to obtain socio-demographic data, medical history and sexual functioning. Sexual function was measure and determine using Malay version of international index of erectile function (MVIIEF) while the ED domain of questionnaire was used to determine the presence and severity of ED. ED was defined based on validated MVIIEF, which states that participant is considered to have ED if ED domain of the MVIIEF score is <25. A total of 220 male participated in the study with a mean age of 37.87±9.85 years. The prevalence of erectile dysfunction among HIV patients was 82.3%. The severity of erectile dysfunction was further categorized into severe (24.1%), moderate (19.1%), mild to moderate (20.9%) and mild (18.3%). In multivariate logistic regression analysis, patients with lower educational background were more likely to be associated with erectile dysfunction (adjusted odds ratio [OR] =2.62, 95% confidence interval [CI] 1.02-6.72). This study reports that erectile dysfunction was prevalent among men on highly HAART. Among adult male HIV patients on HAART regimen, those come from lower education background are associated with higher odds of developing erectile dysfunction. Hence, in managing patients with HIV, physicians should be more alert, and to identify patients with lower education background as such patients are more likely to develop erectile dysfunction.